Antibacterial Activity in Ethanol Extract of Kersen Flowers (Muntingia calabura L.) Against Bacteria Causing Gastrointestinal Tract Infections Using the Agar Diffusion Method - Maryam, St.; Fitriana, Fitriana; Annisa, Nurfiqah (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
The increasing prevalence of antibiotic resistance necessitates the exploration of alternative treatments such as medicinal plants. This study evaluates the antibacterial potential of Kersen flowers (Muntingia calabura L.) against pathogens causing gastrointestinal infections. Aimed at determining the antibacterial effectiveness of ethanol extracts from Kersen flowers, the research tests the activity against Escherichia coli, Salmonella typhi, Vibrio cholerae, and Shigella dysenteriae. Employing the agar diffusion method, various concentrations of the extract (0.05% to 10%) were analyzed. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were also assessed to identify the lowest effective concentrations. The ethanol extract demonstrated significant antibacterial activity; notably, the largest inhibition zone measured 30.74 mm at a concentration of 10%. Effective MICs were as low as 0.1% for all tested bacteria, while MBCs ranged from 0.1% to 0.4%. These results suggest that ethanol extracts of Kersen flowers exhibit potent antibacterial properties against major gastrointestinal pathogens, supporting further exploration of these extracts as a natural antibacterial treatment and offering a potential alternative to conventional antibiotics.